What is the role of adipokines in myasthenia gravis? - Rozmilowska I; Czyzewski D; Mazur B; Adamczyk-Sowa M (Dove Medical Press, 2018)
Izabela Rozmilowska,1 Damian Czyzewski,2 Bogdan Mazur,3 Monika Adamczyk-Sowa1 1Department of Neurology, Medical University of Silesia, Zabrze, Poland; 2Department of Thoracic Surgery, Medical University of Silesia, Zabrze, Poland; 3Department of Microbiology, Medical University of Silesia, Zabrze, Poland Objective: Myasthenia gravis (MG) is a disease with autoimmune etiology. The main pathomechanism is related to the production of antibodies against nicotinic acetylcholine receptor. The present study is aimed to compare the serum level of adipokines in patients with MG with that in controls, as well as to study the relation of these levels with disease severity. Patients and methods: Fifty patients with MG and 30 healthy individuals were enrolled in our study. Serum concentrations of select adipokines, namely adiponectin, leptin, omentin, visfatin, and resistin were measured. Results: The results showed a significant increase in serum concentrations of adiponectin and resistin in the patients with MG compared with the controls. Conclusion: Further studies are warranted to assess changes in adipokine concentration levels in patients with MG. Keywords: adiponectin, leptin, resistin, visfatin, omentin